Microbial Community Composition Associated with Potato Plants Displaying Early Dying Syndrome - Tudor Borza; Rhea Amor Lumactud; So Yeon Shim; Khalil Al-Mughrabi; Balakrishnan Prithiviraj (Microorganisms, 2025)
Potato early dying disease complex (PED) leads to premature senescence and rapid decline in potato plants. Unlike potato wilt caused solely by Verticillium species, PED symptoms are more severe due to the synergistic effects of multiple pathogens, including root-lesion nematodes, fungi such as Colletotrichum and Fusarium, and soft-rot bacteria. To investigate the microbiome responsible for PED, soil and stem samples from healthy-looking and symptomatic plants were analyzed using amplicon-targeted next-generation sequencing (Illumina MiSeq and PacBio technologies). Samples were collected from four locations in New Brunswick, Canada from fields previously rotated with barley or oat. Comparative analysis of the bacterial, fungal, and eukaryotic diversity in soil samples showed minimal differences, with only bacterial alpha diversity influenced by the plant health status. Verticillium dahliae was abundant in all soil samples, and its abundance was significantly higher in the stems of diseased plants. Additional fungal species implicated in PED, including Plectosphaerella cucumerina, Colletotrichum coccodes, Botrytis sp., and Alternaria alternata, were also identified in the stems. This study highlights the complex, plant-associated microbial interactions underlying PED and provides a foundation for microbiome-informed disease management strategies.